The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12884-022-04999-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of low fifth minute Apgar score among newborns delivered by cesarean section at Wolaita Sodo University Comprehensive Specialized Hospital, Southern Ethiopia: an unmatched case control study

Abstract: Background Apgar score is used to evaluate the neonates’ overall status and response to resuscitation, as well as its prognosis beyond the neonatal period. Low fifth minute Apgar scores is more frequent and is associated with markedly increased risks of neonatal mortality and morbidity. In Ethiopia, the prevalence of birth asphyxia is high (22.52%). Birth asphyxia contributes to significant neonatal morbidities and mortalities due to severe hypoxic-ischemic multi-organ damage, mainly brain dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This nding was similar to those of other researchers in, Ethiopia [20] and Western Uganda [22] who found common adverse outcomes to be low Apgar scores (23.1% and 19.2%, respectively). Also, other studies in Ethiopia [14] and [20] indicated NICU admissions of 23.5% and 34.8%, respectively. Additionally, similar ndings regarding FSB were found in studies done in, India[16], Ghana [6], and Uganda [22], with incidences of FSB standing at, 17.4%, 16.4%, and 8.1% respectively.…”
Section: Common Adverse Neonatal Outcomes Among Emergency Obstetrics ...mentioning
confidence: 77%
See 3 more Smart Citations
“…This nding was similar to those of other researchers in, Ethiopia [20] and Western Uganda [22] who found common adverse outcomes to be low Apgar scores (23.1% and 19.2%, respectively). Also, other studies in Ethiopia [14] and [20] indicated NICU admissions of 23.5% and 34.8%, respectively. Additionally, similar ndings regarding FSB were found in studies done in, India[16], Ghana [6], and Uganda [22], with incidences of FSB standing at, 17.4%, 16.4%, and 8.1% respectively.…”
Section: Common Adverse Neonatal Outcomes Among Emergency Obstetrics ...mentioning
confidence: 77%
“…This nding is consistent with ndings from other researchers who noted that antepartum hemorrhage is signi cantly associated with adverse neonatal outcomes. For example, in Ethiopia [14] it noted a 3.96-fold greater risk of having adverse neonatal outcomes than did their counterparts. A study in India [2] also reported that APH contributed to 7.3% of adverse neonatal outcomes.…”
Section: Common Adverse Neonatal Outcomes Among Emergency Obstetrics ...mentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, 92.4% (339) mothers received TT vaccines, 78.5% (288) were given iron supplements, and 40.6% (149) had complications during their current pregnancy. Eclampsia, Antepartum Hemorrhage (APH), and infection were the leading causes of these complications in 19.9% (73), 11.7% (43), and 4.63% (17) of mothers, respectively (Table 2).…”
Section: Obstetrics and Antepartum Related Factorsmentioning
confidence: 99%